2015
DOI: 10.3109/13880209.2015.1057651
|View full text |Cite
|
Sign up to set email alerts
|

Ginger extract modulates Pb-induced hepatic oxidative stress and expression of antioxidant gene transcripts in rat liver

Abstract: Context: Spices and herbs are recognized sources of natural antioxidants that can protect from oxidative stress, thus play an important role in chemoprevention of liver diseases. Ginger is used worldwide primarily as a spicy condiment. Objective: This study evaluated the ability of ginger extract (GE) to ameliorate oxidative-hepatic toxicity induced by lead acetate (PbAc) in rats. Materials and methods: Five groups of animals were used: group I kept as control; groups II, IV, and V received PbAc (1 ppm in drin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
18
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 63 publications
5
18
0
Order By: Relevance
“…Pb concentration in testicular and epididymal tissue samples was measured by atomic absorption spectrophotometry (Perkin‐Elmer Model 400, Shelton, CT, USA) as previously described by Mohamed, El‐Nahas, El‐Sayed, and Ashry (). Serum and testicular concentrations of testosterone were measured by commercial radioimmunoassay (RIA) kit from Immunotech (Beckman Coulter, Marseille, France), and 17β‐oestradiol concentrations were estimated by RIA using Spectria Estradiol RIA kit (Orion Diagnostica Oy, Espoo, Finland) according to the manufacturer's instructions and as previously described (Zamrazilova, Sosvorova, Heracek, Sobotka, & Hampl, ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Pb concentration in testicular and epididymal tissue samples was measured by atomic absorption spectrophotometry (Perkin‐Elmer Model 400, Shelton, CT, USA) as previously described by Mohamed, El‐Nahas, El‐Sayed, and Ashry (). Serum and testicular concentrations of testosterone were measured by commercial radioimmunoassay (RIA) kit from Immunotech (Beckman Coulter, Marseille, France), and 17β‐oestradiol concentrations were estimated by RIA using Spectria Estradiol RIA kit (Orion Diagnostica Oy, Espoo, Finland) according to the manufacturer's instructions and as previously described (Zamrazilova, Sosvorova, Heracek, Sobotka, & Hampl, ).…”
Section: Methodsmentioning
confidence: 99%
“…Catalase (CAT) activity was determined according to the method described by Aebi () and as previously described by Mohamed et al. (). Lipid peroxide (LPO) was estimated spectrophotometrically by measuring the concentration of malondialdehyde (MDA), an end product of LPO, after the reaction with thiobarbituric acid to form thiobarbituric acid‐reactive substances (TBARs), as described by Mabrouk and Ben Cheikh ().…”
Section: Methodsmentioning
confidence: 99%
“…Pb has been found to derail the antioxidant defense system by interfering with the metals that are essential for antioxidant enzyme activities, supporting the role of oxidative stress in lead hepatotoxicity . Recently, a number studies indicated that Pb exposure could induce oxidative stress by increasing ROS and MDA levels and disrupting the activities of some antioxidant enzymes such as SOD, GST, and GSH in different laboratory animals . Reports by Alya et al indicated that MDA levels and SOD activity in the liver and kidney increased significantly in female rats when exposed to 50 mg Pb/l for 40 and 65 days.…”
Section: Discussionmentioning
confidence: 96%
“…Metal‐induced alterations in antioxidant enzyme activities have been extensively studied . Pb has been found to derail the antioxidant defense system by interfering with the metals that are essential for antioxidant enzyme activities, supporting the role of oxidative stress in lead hepatotoxicity . Recently, a number studies indicated that Pb exposure could induce oxidative stress by increasing ROS and MDA levels and disrupting the activities of some antioxidant enzymes such as SOD, GST, and GSH in different laboratory animals .…”
Section: Discussionmentioning
confidence: 99%
“…The identification of a component by its retention time (GC) and fragmentation pattern (MS), along with sample specific information afforded to make GC-MS the foremost confirmation method for analyzing herbal extract [7]. Up to date, gas chromatography-mass spectrometry (GC-MS) has played the most important role in the identification of the chemical composition of medical plants [8][9][10].…”
Section: Introductionmentioning
confidence: 99%